2017
DOI: 10.1016/j.nmni.2016.09.013
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of a new species within Bacillus genus in a stool sample from Gabon: “Bacillus massiliogabonensis” sp. nov.

Abstract: The discovery of new bacteria from the human gut using a culturomics method is a novel field of increasing interest in microbiology. Here the main characteristics of “Bacillus massiliogabonensis” strain Marseille P2639, a new Gram-negative bacterium isolated from the stool sample of a healthy 16-year-old Gabonese boy, are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The gut is analysed mainly by culture-based methods [15]. In this study, examining 10 [16,17,18,19]. Other studies have also reported the presence of Escherichia coli, Klebsiella pneumonia and Staphylococcus aureus in human faeces [20,21,22].…”
Section: Discussionmentioning
confidence: 98%
“…The gut is analysed mainly by culture-based methods [15]. In this study, examining 10 [16,17,18,19]. Other studies have also reported the presence of Escherichia coli, Klebsiella pneumonia and Staphylococcus aureus in human faeces [20,21,22].…”
Section: Discussionmentioning
confidence: 98%
“…A culturing approach that uses high-throughput culture conditions in combination with matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry and 16S rRNA sequencing for taxonomic identification and referred to as culturomics has allowed significant increase in a number of bacteria discovered in human GIT including species known in humans but not in the gut, species previously considered unculturable as well as new species. Considerable part of them is represented by Firmicutes ( Lagier et al, 2016 ) including Bacillus species ( Lagier et al, 2015 ; Mourembou et al, 2016 ; Senghor et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%